Community patch dynamics governs direct and indirect nutrient recycling by aggregated animals across spatial scales. (12th January 2022) - Atkinson, Carla L.; Forshay, Kenneth J.
Abstract: Animals can have pervasive effects on ecosystems as they modify their biogeochemical and physical environments. In particular, when animals occur in high densities these effects can result in dramatic changes in the physical environment and biogeochemical hotspots or hot moments. While most research to date has focused on the direct role of animals in biogeochemical cycles, few have examined how animals indirectly influence biogeochemical cycles across scales. Freshwater mussels occur as spatially heterogeneous, dense and species‐rich aggregations in many river ecosystems world‐wide. Here we examined how mussel communities (a) directly influence the flux of particulate and dissolved nutrients and (b) indirectly effect the flux of N2 production, via denitrification, across a gradient of mussel biomass and differences in community composition at the patch‐ (0.25 m 2 ) and stream reach‐scales (60–80 m). We combined measurements of ammonia (N) and soluble reactive phosphorous (P) excretion and C, N and P biodeposition rates for 10 species with biomass and distribution estimates for seven mixed‐species aggregations to quantify direct mussel contributions to biogeochemical cycling and the spatial heterogeneity of their impact. Additionally, we sampled sediments at a fine spatial scale to determine how mussel biomass and richness influence potential denitrification (indirect flux) rates at the patch‐ and reach‐scales. We predicted that increasing mussel biomass would lead to greater direct and indirect fluxes of nutrients, manifesting in heterogeneous nutrient redistribution within and among stream reaches. We also predicted that variation in community composition would result in differential nutrient excretion and egestion stoichiometries. Our results indicate that mussel aggregations directly influence soluble and particulate nutrient fluxes with community composition, particularly phylogenetic tribe composition, controlling the stoichiometry. Mussel aggregations also indirectly influenced nutrient fluxes as greater mussel biomass and species richness resulted in higher denitrification rates as mediated by their interactions with the sediments and enhancement of nutrient availability. Our results underscore the importance of patchy communities in acting as biogeochemical control points. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.